Respons Kognitif, Afektif, Dan Konatif Mahasiswi Terhadap Konten Youtube Tasya Farasya - Putri Sonya; Nur Putri Ramadhani; Saladin Saladin (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the cognitive, affective, and conative responses of female students at STISIPOL Candradimuka to Tasya Farasya’s YouTube content in the episode “Belanja Bulanan - First Impression”. This research employed a descriptive qualitative approach using media effects theory as the analytical framework. Data were collected through in-depth interviews with eight female student informants, content observation, documentation, and literature study. The findings show that cognitively the content increases audience knowledge regarding product types, functions, prices, textures, and usage results. Affectively, the content generates interest, entertainment, and curiosity, although some informants responded neutrally. Conatively, the content encourages some informants to seek further information, consider purchasing, try products, or discuss the video with friends. These findings indicate that young audiences are not passive recipients; rather, they actively evaluate message credibility, compare information sources, and adjust their responses according to personal needs.Respons Audiens, Efek Media, Youtube, Beauty Vlogger.